Characterization of Three New Glutaredoxin Genes in the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis: Putative Role of RiGRX4 and RiGRX5 in Iron Homeostasis - Tamayo, Elisabeth (PLoS One, 2016)
Glutaredoxins (GRXs) are small ubiquitous oxidoreductases involved in the regulation of the redox state in living cells. In an attempt to identify the full complement of GRXs in the arbuscular mycorrhizal (AM) fungus Rhizophagus irregularis, three additional GRX homologs, besides the formerly characterized GintGRX1 (renamed here as RiGRX1), were identified. The three new GRXs (RiGRX4, RiGRX5 and RiGRX6) contain the CXXS domain of monothiol GRXs, but whereas RiGRX4 and RiGRX5 belong to class II GRXs, RiGRX6 belongs to class I together with RiGRX1. By using a yeast expression system, we observed that the newly identified homologs partially reverted sensitivity of the GRX deletion yeast strains to external oxidants. Furthermore, our results indicated that RiGRX4 and RiGRX5 play a role in iron homeostasis in yeast. Gene expression analyses revealed that RiGRX1 and RiGRX6 were more highly expressed in the intraradical (IRM) than in the extraradical mycelium (ERM). Exposure of the ERM to hydrogen peroxide induced up-regulation of RiGRX1, RiGRX4 and RiGRX5 gene expression. RiGRX4 expression was also up-regulated in the ERM when the fungus was grown in media supplemented with a high iron concentration. These data indicate the two monothiol class II GRXs, RiGRX4 and RiGRX5, might be involved in oxidative stress protection and in the regulation of fungal iron homeostasis. Increased expression of RiGRX1 and RiGRX6 in the IRM suggests that these GRXs should play a key role in oxidative stress protection of R. irregularis during its in planta phase.